Empowering Woman Through the Sharia Savings and Loan Program in an Effort to Survive During the Covid-19 Pandemic - Setiaji, Eko (UIN Sunan Ampel Surabaya, 2022)
The Covid-19 pandemic has encourage more women not to return to work during the pandemic. This adversely affects not only women's welfare but also economic progress and women's independence. The Sharia Borrowing Program from the Sharia Cooperatives assisted by Rumah Zakat is one of the efforts to provide capital to women who have micro businesses in order to be able to maintain their business activities during the Covid-19 pandemic. This study aims to determine the impact of empowering women by Rumah Zakat through the sharia savings and loan program during the Covid-19 pandemic. This research is a descriptive research and uses a qualitative approach. The data collection method used in-depth interviews conducted to 12 members of BUMMas, Village Officer, Relawan Inspirasi and the management of the Mitra Insan Mandiri Cooperative in Gilingan Village and the Berkah Bersama Cikeusik Cooperative in Pandeglang Regency. The results of the study show that women who are members of savings and loan groups are able to take advantage of interest-free financing to maintain their economic business so as not to go out of business during the Covid-19 pandemic. Savings and loan activities are also able to educate members to set aside income as member savings in cooperatives so that they can become future savings. Through regular member coaching, there is a change in the mindset of members to no longer access loans to moneylenders who pay high interest. Keywords: Covid-19 Pandemic, Women Empowerment, Sharia Savings and Loan Program